Toleransi Beragama Di Era Disrupsi: Potret Masyarakat Multikultural Sumatera Utara - Toguan Rambe; Seva Maya Sari (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
North Sumatra is known as a heterogeneous society as well as other provinces in Indonesia, diversity is seen in differences in religion, culture and so forth. This condition certainly has the potential to cause social conflict to disrupt religious harmony. On the other hand, North Sumatra is known as a province that is wise in handling socio-religious conflicts that occur in society. This study uses a qualitative approach in which the type of research is phenomenology (phainomenon). In collecting data, the author uses the method of observation and direct interviews which are both participative and non-participative, namely observations involving religious leaders and officials who have authority in religious institutions in North Sumatra. The conclusions in this study noted that the portrait of diversity was seen in religious and cultural entities. The diversity of religions in this region is recorded that there are 6 religions served by the government, namely Islam 65.45%, Christian 26.62%, Catholic 4.78%, Hindu 0.19%, Buddhist 2.82%, Confucianism 0, 14%. Cultural entities recorded that there were eight ethnic groups added with several ethnic immigrants. The eight indigenous ethnicities are Malay, Batak Toba, Batak Angkola, Mandailing, Simalungun, Karo, Nias, and Pakpak / Dairi. Meanwhile, the potential of this area in realizing a tolerant life is the use of religious values and local wisdom as a means of establishing a tolerant attitude. And support from the government, religious leaders and the availability of communication platforms between religious leaders such as FKUB.